Impact of obesity on safety outcomes and treatment modifications with ado-trastuzumab emtansine in breast cancer patients. (January 2022) - Lee, Anna; Larck, Chris; Moore, Donald C
Introduction: Ado-trastuzumab emtansine (T-DM1) is an antibody-drug conjugate indicated for the treatment of HER2-positive breast cancer. The 2012 American Society of Clinical Oncology guidelines on chemotherapy dosing in obesity recommend using full weight-based cytotoxic chemotherapy doses to treat obese patients with cancer. These guidelines were published prior to the advent of anticancer antibody-drug conjugates. There is a need to investigate the safety of T-DM1 in obese patients. Methods: This retrospective chart review included adult patients with breast cancer receiving T-DM1. The primary endpoint was a composite of the incidence of T-DM1 treatment modifications secondary to an adverse event. Secondary outcomes included the incidence of dose reductions, dose delays, treatment discontinuations, and adverse events. Results: A total of 119 patients with HER2-positive breast cancer who received T-DM1 therapy were included in this study: 44 obese patients and 75 non-obese patients. The composite outcome of treatment modifications due to toxicity was significantly higher in obese patients compared to non-obese patients (45% vs 25%, p = 0.024). Treatment delays were significantly higher in obese patients (36% vs 16%, p = 0.011). All-grade adverse events with a higher incidence in obese patients included left ventricular ejection fraction decrease (11% vs 5%), bilirubin increase (32% vs 12%), thrombocytopenia (61% vs 55%), and peripheral neuropathy (34% vs 27%). Conclusions: This study suggests obese patients receiving T-DM1 may require more treatment modifications secondary to adverse events compared to non-obese patients. Larger studies are needed to determine if obese patients are at higher risk for specific T-DM1-induced adverse events.